Performance Of An Alumina Ball Packed Bed Porous Media Burner Fueled By Producer Gas - Ho, John Chung Eng (2012)

(untitled)
Producer gas from biomass gasification is unable to burn efficiently in conventional burner due to low burning velocity of CO which comprises of about 20% of the producer gas. Porous media burner (PMB) is a promising technology for improving combustor performance that could solve the problem. The study aims to investigate the performance of PMB fueled by producer gas from biomass gasification. A stratified throatless downdraft gasifier was used to generate producer gas with heating value of about 4-5 MJ m-3. Investigation has been done on a 2-layer alumina balls packed bed PMB with first and second layer consist of 10 mm and 20mm alumina balls respectively.